Exercise prevents fructose-induced hypertriglyceridemia in healthy young subjects. - Egli, L; Lecoultre, V; Theytaz, F; Campos, V; Hodson, L; Schneiter, P; Mittendorfer, B; Patterson, B; Fielding, B; Gerber, P; Giusti, V; Berneis, K; et al. (2013)
Excess fructose intake causes hypertriglyceridemia and hepatic insulin resistance in sedentary humans. Since exercise improves insulin sensitivity in insulin-resistant patients, we hypothesized that it would also prevent fructose-induced hypertriglyceridemia. This study was therefore designed to evaluate the effects of exercise on circulating lipids in healthy subjects fed a weight-maintenance, high-fructose diet. Eight healthy males were studied on three occasions after 4 days of 1) a diet low in fructose and no exercise (C), 2) a diet with 30% fructose and no exercise (HFr), or 3) a diet with 30% fructose and moderate aerobic exercise (HFrEx). On all three occasions, a 9-h oral [(13)C]-labeled fructose loading test was performed on the fifth day to measure [(13)C]palmitate in triglyceride-rich lipoprotein (TRL)-triglycerides (TG). Compared with C, HFr significantly increased fasting glucose, total TG, TRL-TG concentrations, and apolipoprotein (apo)B48 concentrations as well as postfructose glucose, total TG, TRL-TG, and [(13)C]palmitate in TRL-TG. HFrEx completely normalized fasting and postfructose TG, TRL-TG, and [(13)C]palmitate concentration in TRL-TG and apoB48 concentrations. In addition, it increased lipid oxidation and plasma nonesterified fatty acid concentrations compared with HFr. These data indicate that exercise prevents the dyslipidemia induced by high fructose intake independently of energy balance.